2017
DOI: 10.4149/bll_2017_012
|View full text |Cite
|
Sign up to set email alerts
|

The detection of curcumins’ antitumoral effects via argyrophilic nucleolar organizing region-associated protein synthesis in mice with ehrlich’s ascitic carcinoma

Abstract: BACKGROUND: Curcumin is a polyphenol compound that has antioxidant, anticancer, anti-infl ammatory, antihyperlipidemic and antimicrobial effects. Nucleolar-organizing regions are the sites of the gene on chromosomes. The present study was aimed to show the antitumoral effect of curcumin via AgNOR protein synthesis in Ehrlich's ascitic carcinoma (EAC) bearing mice. METHODS: Twenty three mice with EAC were randomly divided into 3 groups as positive control (n = 7), group 2 (n = 8) and 3 (n = 8) treated intraperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…In addition, an appropriate increase in the use of dose is also a conventional method. Curcumin (50 or 100 mg/kg BW) has been shown to attenuate diseases, EMT and tumor process in animal studies (Afrin et al, ; Goncalves Vde et al, ; Momeni and Eskandari, ; Nisari et al, ; Yuan et al, ). Studies from our laboratory have also suggested that 100 mg/kg BW curcumin restored tobacco smoke‐induced EMT in the mice stomach and bladder tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an appropriate increase in the use of dose is also a conventional method. Curcumin (50 or 100 mg/kg BW) has been shown to attenuate diseases, EMT and tumor process in animal studies (Afrin et al, ; Goncalves Vde et al, ; Momeni and Eskandari, ; Nisari et al, ; Yuan et al, ). Studies from our laboratory have also suggested that 100 mg/kg BW curcumin restored tobacco smoke‐induced EMT in the mice stomach and bladder tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to identify new biomarkers to differentiate benign and malignant lesions. In addition, the selection of the most reliable therapeutic strategy for cancer treatment is very important for the management of the treatment strategy and to improve success (16,18,36). We aimed to determine the average number of AgNOR in our study.…”
Section: Discussionmentioning
confidence: 99%
“…These regions are composed of ribosomal DNA (rDNA) and some proteins with argyrophilic properties. These regions are copied to the ribosomal RNA, which is transformed into the immature ribosomes in the nucleolus and mature ribosomes in the cytoplasm, respectively (16). These regions can be stained with silver, when active.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental studies, experimental animals are frequently used for clinical observations [7,8]. In animal experiments for cancer treatments, often plant extracts have an important place in research [9][10][11].…”
Section: Diagnosis Of Cancer Causes Psychological Problems and Medicalmentioning
confidence: 99%